Ex-post effects of circuit breakers in crisis and calm markets: long horizon evidence from wide-band Malaysian price limits - Sifat, Imtiaz Mohammad; Mohamad, Azhar (Emerald Group Publishing Ltd., 2020)
Purpose – Despite regulatory claims of straitening volatility and preventing crashes, evidences on circuit breakers’ ability to achieve so are nonconclusive. While previous scholars studies general performances of circuit breakers, the authors examine whether Malaysian price limits aggravate volatility, impede price discovery, and interfere with trading activities in both tranquil and stressful periods. Design/methodology/approach – The study uses a combination of parametric and nonparametric techniques consistent with Kim and Rhee (1997) to examine the major ex-post hypotheses in circuit breaker research. Findings – For calm markets, the authors find significant success of upper limits in tempering volatility with low trading interference. Lower limits show mixed results. Conversely, in crisis markets limits fare poorly in nearly all aspects, particularly for lower limits. Practical implications – Ramifications of the paper’s findings are discussed through highlighting the asymmetric nature of price limits’ ex-post effects. The paper also contributes to regulatory debate surrounding the quest for an optimal price limit. Originality/value – The paper is the first of its kind in documenting long-horizon evidence of ex-post effects of a wide-band price limit. Moreover, the paper is unique in its approach in bifurcating circuit breaker performance along the line of market stability periods.